Biomimetic architecture: Biological Research Center, Hospital de Navarra. Spain - Espinoza De La Grecca, Luis (2022)
The biomimetic architecture seeks sustainable solutions in nature, without purely replicate their ways, but through the understanding of the rules that govern them, using design ideas in structures and facades. Explain how they can transfer those ideas of the natural world to an architectural project as is the case of the Biological Research Center of the Hospital of Navarra in Spain.